2019
DOI: 10.1002/ddr.21588
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of l‐arginine‐nitric oxide pathway in the antidepressant and memory promoting effects of morin in mice

Abstract: l‐Arginine‐nitric oxide pathway has been reported to be involved in the mediation of the psychopharmacological effects of many psychotropic drugs. Previous studies have shown that morin, a psychotropic compound isolated from mulberry leaf produces functional psychopharmacological effects indicative of antidepressant, antipsychotic, anxiolytic and nootropic properties. However, the role of l‐arginine‐nitric oxide pathway in the psychotropic effects of morin has not been fully investigated, hence, the need for t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 50 publications
0
7
0
Order By: Relevance
“…However, animals pretreated with flumazenil before CP (100 mg/kg) or DZP inhibited their anticonvulsant activity (Table 2). In another experiment, the modulatory role of the nitric oxide‐cGMP pathway on CP‐induced anticonvulsant activity was examined (Ben‐Azu, Aderibigbe, Ajayi, Umukoro, & Iwalewa, 2019). While L‐arginine alone prolonged the duration of PTZ‐induced seizures (Table 2), the administration of L‐arginine before CP (100 mg/kg) significantly reduced the seizure threshold in comparison with CP‐only treatment (Table 2).…”
Section: Resultsmentioning
confidence: 99%
“…However, animals pretreated with flumazenil before CP (100 mg/kg) or DZP inhibited their anticonvulsant activity (Table 2). In another experiment, the modulatory role of the nitric oxide‐cGMP pathway on CP‐induced anticonvulsant activity was examined (Ben‐Azu, Aderibigbe, Ajayi, Umukoro, & Iwalewa, 2019). While L‐arginine alone prolonged the duration of PTZ‐induced seizures (Table 2), the administration of L‐arginine before CP (100 mg/kg) significantly reduced the seizure threshold in comparison with CP‐only treatment (Table 2).…”
Section: Resultsmentioning
confidence: 99%
“…L‐arginine was metabolized into many bioactive molecules in a tightly regulated manner in mammals (Morris, 2007 ). L‐arginine produced NO through nitric oxide synthase (Nos) (Paul & Ekambaram, 2011 ), including endothelial Nos (eNos), neuronal Nos (nNos), and inducible Nos (iNos) (Ben‐Azu et al., 2019 ; Zhang et al., 2013 ). eNos loss contributed to APP amyloid formation processes and cognitive decline (Bergin et al., 2018 ), nNos played a vital role in synaptic plasticity and learning and memory (Paul & Ekambaram, 2011 ), while iNos could act as proinflammatory agents (Haj‐Mirzaian et al., 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…eNos loss contributed to APP amyloid formation processes and cognitive decline (Bergin et al., 2018 ), nNos played a vital role in synaptic plasticity and learning and memory (Paul & Ekambaram, 2011 ), while iNos could act as proinflammatory agents (Haj‐Mirzaian et al., 2016 ). NO was also involved in synaptic plasticity, long‐term potentiation, and memory consolidation (Ben‐Azu et al., 2019 ). NO deficiency promoted endothelial dysfunction, accelerated amyloid formation and accumulation, reduced synaptic plasticity, activated microglia, and induces neuroinflammation (Katusic & Austin, 2014 ).…”
Section: Discussionmentioning
confidence: 99%
“…The results also indicated its possible role in inflammasome activation, as morin reduced levels of the inflammasome pathway markers TNF-α, IL-1β, toll-like receptor-4 (TLR-4), NLRP3, and caspase-1, indicating its promising potential in alleviating the inflammatory basis of the disease [ 264 ]. Another study performed on mice suggested that the antidepressant effects of morin could be mediated through the L-arginine-NO pathway, as beneficial effects of morin on despair-like behavior were reversed by the NO precursor L-arginine [ 265 ].…”
Section: Antidepressant Effects Of Flavonolsmentioning
confidence: 99%